Seroconversion and outcomes after initial and booster COVID‐19 vaccination in adults with hematologic malignancies. Issue 18 (11th July 2022) - Ollila, Thomas A.; Masel, Rebecca H.; Reagan, John L.; Lu, Shaolei; Rogers, Ralph D.; Paiva, Kimberly J.; Taher, Rashida; Burguera‐Couce, Ella; Zayac, Adam S.; Yakirevich, Inna; Niroula, Rabin; Barth, Peter; et al.
Abstract : Background: Patients with hematologic malignancies have impaired humoral immunity secondary to their malignancy and its treatment, placing them at risk of severe coronavirus disease‐19 (COVID‐19) infection and reduced response to vaccination. Methods: The authors retrospectively analyzed serologic responses to initial and booster COVID‐19 vaccination in 378 patients with hematologic malignancy and subsequently tracked COVID‐19–related outcomes. Results: Seroconversion occurred in 181 patients (48%) after initial vaccination; patients who had active malignancy or those who were recently treated with a B‐cell–depleting monoclonal antibody had the lowest rates of seroconversion. For initial nonresponders to vaccination, seroconversion after a booster dose occurred in 48 of 85 patients (56%). The seroconversion rate after the booster was similar for patients on (53%) and off (58%) active therapy ( p  = .82). Thirty‐three patients (8.8%) developed a COVID‐19 infection, and there were three COVID‐19–related deaths (0.8%). Although no significant association was observed between postvaccination seroconversion and the incidence of COVID‐19 infection, no patient with seroconversion died from COVID‐19, and no patient who received tixagevimab/cilgavimab ( N  = 25) was diagnosed with a COVID‐19 infection. Conclusions: Booster vaccinations can promote seroconversion in a significant proportion of patients who are seronegative after the initial vaccination course regardless of the specific vaccine or on/off treatment status at the time of revaccination. Although postvaccination seroconversion may not be associated with a decrease in any (including asymptomatic) COVID‐19 infection, the authors' experience suggested that effective vaccination (including a booster), supplemented by passive immunization using tixagevimab/cilgavimab in case of lack of seroconversion, effectively eliminated the risk of COVID‐19 death in the otherwise high‐risk population. Lay summary: Patients with hematologic malignancy, especially lymphoma, have an impaired response to coronavirus disease 2019 (COVID‐19) vaccination. In this single‐institution review, less than one half of the patients studied made detectable antibodies. For those who did not make detectable antibodies after initial vaccination, over one half (65%) were able to produce antibodies after booster vaccination. By the end of February 2022, 33 of the original 378 patients had a documented COVID‐19 infection. The only deaths from COVID‐19 were in those who had undetectable antibodies, and no patient who received prophylactic antibody therapy developed a COVID‐19 infection. Abstract : Hematologic malignancies and their treatments impaired humoral immunity from coronavirus disease 2019 vaccination, and booster vaccine overcame a lack of initial response in 58% of patients, including 63% those on active therapy. The findings indicated that booster vaccinations should be strongly encouraged; however, even with boosters, many remain unprotected, which should inform infection prevention and treatment strategies.